The Catch-22 of Pharmacy Practice in Pakistan's Pharmacy Education - Atta Abbas (MDPI AG, 2014)
New developments in the pharmacy education structure in Pakistan led to the formation of a separate department grouping high specialized services/subjects. However, inadequate planning has exposed a vacuity, as the educational authorities failed to develop a workforce before creating the specialized department. As a result, this vacuum is on the verge of being impinged by pharmacy professionals specialized in entirely different domains which would be detrimental to the future prospects of the development of pharmacy practice in Pakistan.